Oxidation of Sperm DNA and Male Infertility - Leila Rashki Ghaleno; AliReza Alizadeh; Joël R. Drevet; Abdolhossein Shahverdi; Mojtaba Rezazadeh Valojerdi (Antioxidants, 2021)
One important reason for male infertility is oxidative stress and its destructive effects on sperm structures and functions. The particular composition of the sperm membrane, rich in polyunsaturated fatty acids, and the easy access of sperm DNA to oxidative damage due to sperm cell specific cytologic and metabolic features (no cytoplasm left and cells unable to mount stress responses) make it the cell type in metazoans most susceptible to oxidative damage. In particular, oxidative damage to the spermatozoa genome is an important issue and a cause of male infertility, usually associated with single- or double-strand paternal DNA breaks. Various methods of detecting sperm DNA fragmentation have become important diagnostic tools in the prognosis of male infertility and such assays are available in research laboratories and andrology clinics. However, to date, there is not a clear consensus in the community as to their respective prognostic value. Nevertheless, it is important to understand that the effects of oxidative stress on the sperm genome go well beyond DNA fragmentation alone. Oxidation of paternal DNA bases, particularly guanine and adenosine residues, the most sensitive residues to oxidative alteration, is the starting point for DNA damage in spermatozoa but is also a danger for the integrity of the embryo genetic material independently of sperm DNA fragmentation. Due to the lack of a spermatozoa DNA repair system and, if the egg is unable to correct the sperm oxidized bases, the risk of de novo mutation transmission to the embryo exists. These will be carried on to every cell of the future individual and its progeny. Thus, in addition to affecting the viability of the pregnancy itself, oxidation of the DNA bases in sperm could be associated with the development of conditions in young and future adults. Despite these important issues, sperm DNA base oxidation has not attracted much interest among clinicians due to the lack of simple, reliable, rapid and consensual methods of assessing this type of damage to the paternal genome. In addition to these technical issues, another reason explaining why the measurement of sperm DNA oxidation is not included in male fertility is likely to be due to the lack of strong evidence for its role in pregnancy outcome. It is, however, becoming clear that the assessment of DNA base oxidation could improve the efficiency of assisted reproductive technologies and provide important information on embryonic developmental failures and pathologies encountered in the offspring. The objective of this work is to review relevant research that has been carried out in the field of sperm DNA base oxidation and its associated genetic and epigenetic consequences.